2020
DOI: 10.3389/fimmu.2020.579889
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional Gene Regulatory Networks in Chronic Airway Inflammatory Diseases: In silico Mapping of RNA-Binding Protein Expression in Airway Epithelium

Abstract: Background: Posttranscriptional gene regulation (PTGR) contributes to inflammation through alterations in messenger RNA (mRNA) turnover and translation rates. RNA-binding proteins (RBPs) coordinate these processes but their role in lung inflammatory diseases is ill-defined. We evaluated the expression of a curated list of mRNA-binding RBPs (mRBPs) in selected Gene Expression Omnibus (GEO) transcriptomic databases of airway epithelium isolated from chronic obstructive pulmonary disease (COPD), severe asthma (SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 121 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…Recent studies are increasingly reporting the loss of several RBPs in in vitro and mouse models of cellular senescence, such as HuD (197), fragile X-related protein 1 (FXR1) (198), and cold shock domain containing E1 (CSDE1)/upstream of N-Ras (UNR) (199). The identification of a global RBP downregulation in two COPD bronchiolar epithelium transcriptomic databases (50) further connects these evidence to a role of AUF-1 in inflammaging through mechanisms yet to be uncovered, likely also related to its extracellular transfer in exosomes. Epithelial-derived exosomes and MV -which were detected, measured and then visualized by TEM in this studycontribute to lung inflammatory disease pathogenesis and the ensuing systemic component through multiple mechanisms (200)(201)(202)(203)(204).…”
Section: Senataxinmentioning
confidence: 65%
See 2 more Smart Citations
“…Recent studies are increasingly reporting the loss of several RBPs in in vitro and mouse models of cellular senescence, such as HuD (197), fragile X-related protein 1 (FXR1) (198), and cold shock domain containing E1 (CSDE1)/upstream of N-Ras (UNR) (199). The identification of a global RBP downregulation in two COPD bronchiolar epithelium transcriptomic databases (50) further connects these evidence to a role of AUF-1 in inflammaging through mechanisms yet to be uncovered, likely also related to its extracellular transfer in exosomes. Epithelial-derived exosomes and MV -which were detected, measured and then visualized by TEM in this studycontribute to lung inflammatory disease pathogenesis and the ensuing systemic component through multiple mechanisms (200)(201)(202)(203)(204).…”
Section: Senataxinmentioning
confidence: 65%
“…This finding was specific for the epithelium, as neither other structural cells (endothelium, fibroblasts) or immune cells (macrophages, infiltrating leukocytes) displayed this difference, nor the levels of the RNA binding proteins Tristetraprolin (TTP) and HuR were changed in the ex vivo and in vitro models (48). We again documented changes in AUF-1 expression in COPD in silico within the identification of a global downregulation for a curated list of 600 RBPs (49) in two COPD bronchiolar epithelium transcriptomic databases (50). The downregulated RBP expression pattern was significantly represented for several pathogenic COPD pathways by Genome Ontology (GO) analysis, expanding relevance of RBP biology in chronic lung inflammation beyond a single member.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, in silico analysis has documented alterations in AUF-1 expression in COPD [25]. This was observed in the context of a global downregulation trend across a curated list of 600 RNA-binding proteins (RBPs) in two transcriptomic databases focusing on the COPD bronchiolar epithelium [26]. The identified downregulated expression pattern of RBPs, including AUF-1, holds significance as it was found to be notably associated with various pathogenic pathways implicated in COPD [27].…”
Section: Discussionmentioning
confidence: 93%
“…Although this suggests that AUF1 may regulate the expression of inflammatory genes involved in COPD, direct regulation by AUF1 of these downstream mRNA, and its implications for the pathogenesis of COPD, remain to be investigated. Recently, a mapping profile of RBPs indicated that most RBP genes are downregulated in the small airway epithelium of those with COPD, comparing to non-smokers and smokers [ 147 ]. Overall, these studies raise the possibility that RBPs may be involved in the development of COPD.…”
Section: Post-transcriptional Regulation In Copdmentioning
confidence: 99%